Serous psammocarcinoma of the ovary: case report with systematic review - Mihaylov, Ilia; Yordanov, Angel; Strateva, Diana; Malkodanski, Ivan (Medical Studies/Studia Medyczne, 2021)
Psammocarcinoma is a rare subtype of serous epithelian neoplasms arising from the ovaries and the peritoneum. It is characterized by massive psammoma body formation, low-grade cytological features, and invasiveness. We present a case of a 59-year-old female diagnosed with relapse of ovarian psammocarcinoma. She was operated 4 years previously and did not undergo chemotherapy. We performed a systematic search on this topic using the PubMed and ScienceDirect databases. In the literature 33 cases of ovarian psammocarcinoma are reported. We discuss the clinicopathological features of these patients. Ovarian psammocarcinoma is a rare and not well described disease. Due to the small number of cases found in the literature, no conclusions can be drawn about the tumour characteristics.